2015
DOI: 10.1007/s10295-014-1538-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the metabolic engineering of Corynebacterium glutamicum for the production of lactate and succinate from renewable resources

Abstract: Recent increasing attention to environmental issues and the shortage of oil resources have spurred political and industrial interest in the development of environmental friendly and cost-effective processes for the production of bio-based chemicals from renewable resources. Thus, microbial production of commercially important chemicals is viewed as a desirable way to replace current petrochemical production. Corynebacterium glutamicum, a Gram-positive soil bacterium, is one of the most important industrial mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 93 publications
0
15
0
Order By: Relevance
“…To solve this problem, key enzymes involved in the acetate production pathway, such as phosphotransacetylase ( pta ), acetate kinase ( ackA ), acetyl‐CoA:CoA transferase ( cat ), and pyruvate:menaquinone oxidoreductase ( pqo ), were deleted. Overexpression of anaplerotic enzymes encoding mutated pyruvate carboxylase ( pyc P458S) and phosphoenolpyruvate carboxylase increased the availability of oxaloacetate and resulted in the production of 9.7 g L −1 . Acetate is the main byproduct competing with succinate production under aerobic conditions, so heterologous expression of acetyl‐CoA synthase from B. subtilis for recycling acetate and overexpression of citrate synthase ( gltA ) increased the production of succinate up to 28.1 g L −1 (Fig.…”
Section: Production Of Polyamide Monomersmentioning
confidence: 99%
See 2 more Smart Citations
“…To solve this problem, key enzymes involved in the acetate production pathway, such as phosphotransacetylase ( pta ), acetate kinase ( ackA ), acetyl‐CoA:CoA transferase ( cat ), and pyruvate:menaquinone oxidoreductase ( pqo ), were deleted. Overexpression of anaplerotic enzymes encoding mutated pyruvate carboxylase ( pyc P458S) and phosphoenolpyruvate carboxylase increased the availability of oxaloacetate and resulted in the production of 9.7 g L −1 . Acetate is the main byproduct competing with succinate production under aerobic conditions, so heterologous expression of acetyl‐CoA synthase from B. subtilis for recycling acetate and overexpression of citrate synthase ( gltA ) increased the production of succinate up to 28.1 g L −1 (Fig.…”
Section: Production Of Polyamide Monomersmentioning
confidence: 99%
“…To increase the carbon flux towards succinic acid production, ldhA and pyc were deleted and 146 g L −1 succinic acid was produced (Table ) . The deletion of genes responsible for acetate ( pqo, pta, ackA, and cat ) production is also required to reduce acetate byproduct formation under anaerobic conditions . To increase the C3 carboxylation efficiency for succinate production, mutant pyruvate carboxylase ( pyc P458S ) was integrated into the chromosomal Δ pta‐ack A locus .…”
Section: Production Of Polyamide Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…The fermentation process of succinic acid production is a novel and green technology, because CO 2 is consumed during the process (Akhtar, Idris, & Aziz, ; Song & Lee, ; Zeikus et al, ). It was believed that the production of succinic acid by microbial fermentation will be conductive to reduce CO 2 accumulation through reducing emissions and recycling of CO 2 , which is released when fossil fuels are combusted (Tsuge, Hasunuma, & Kondo, ). Therefore, in order to make the succinic acid production process more efficient and cost‐effective, the development of suitable microorganism is critically important.…”
Section: Introductionmentioning
confidence: 99%
“…Sever C. glutamicum strains had been developed to produce succinic acid (Kawaguchi, Vertès, Okino, Inui, & Yukawa, ; Okino et al, ; C. Wang et al, ; Zhou et al, ). It was suggested that the potential exists on the use of C. glutamicum as a potential cell factory for producing succinic acid (Tsuge et al, ). As another Corynebacterium sp ., it was found that C. crenatum could produce succinic acid and lactic acid at high cell density when the strain was incubated under anaerobic conditions, and the organic acid production rate could sustain long time (Chen et al, ; Chen, Wu, Jiang, & Li, ).…”
Section: Introductionmentioning
confidence: 99%